(untitled) (PIONIR: JURNAL PENDIDIKAN, 2020)
This study aims to describe how bullying behavior and the motives of the bulliers. The research subjects were 5 victim students and 6 bullier students who came from grades IV and V of MI Negeri 2 Aceh Tamiang. The data collection technique using in-depth interviews and observations. The results of the study show the forms of bullying behavior, such as: verbal bullying (taunting and labeling). Physical bullying (pinching and pulling the veil), and indirect bullying (asking others to hurt). The motives of the bullier for bullying, among others, are feeling superior, resentful, and jealous.